Life-Changing Events in the Practice of a Homeopath: Emily Howard Jennings Stowe - Nash, Carol (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
Emily Howard Jennings Stowe is acclaimed as Canada’s first white openly female physician to practice medicine. This assessment of Stowe’s accomplishment is accurate because she practiced in the 19th century. However, by today’s definition of a physician, Stowe practiced homeopathy, since she did not engage in standardized allopathic medicine. Yet, no assessment of Stowe’s life-changing events developing her as a homeopath has been attempted until now. A unique narrative process following the tradition of psychoanalytic narratology is engaged based on responses to questions posed regarding her life, from those most objective and specific to those more subjective and general. This follows a prescribed order of question-asking: when, where, who, what, how, and why. The aim is to facilitate comparison and an interpretation of connections regarding her life-changing events as a homeopath. It is found that much of Stowe’s success originated from her family’s upper-class connections, and her Quaker religion’s belief in the intellectual equality of women to men, promoting her studious nature and encouraging her homeopathic education at home and in the United States. There were periods in her life that might have ended her career; however, the protective features of her status permitted her to withstand these difficulties successfully.